2017
DOI: 10.1002/2017gl072912
|View full text |Cite
|
Sign up to set email alerts
|

Transient brightening of Jupiter's aurora observed by the Hisaki satellite and Hubble Space Telescope during approach phase of the Juno spacecraft

Abstract: In early 2014, continuous monitoring with the Hisaki satellite discovered transient auroral emission at Jupiter during a period when the solar wind was relatively quiet for a few days. Simultaneous imaging made by the Hubble Space Telescope (HST) suggested that the transient aurora is associated with a global magnetospheric disturbance that spans from the inner to outer magnetosphere. However, the temporal and spatial evolutions of the magnetospheric disturbance were not resolved because of the lack of continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 59 publications
(106 reference statements)
2
53
1
Order By: Relevance
“…The disappearance of the recurrent aurora on DOY −17 could also be associated with the decrease in the mass loading from DOY −34 to DOY 0. These observational results do not contradict implications that the transient aurora and energetic event are likely associated with the mass loading and are basically independent of the solar wind; that is, they are “internally driven” processes, as recently argued in Kimura et al (, ) and other studies.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The disappearance of the recurrent aurora on DOY −17 could also be associated with the decrease in the mass loading from DOY −34 to DOY 0. These observational results do not contradict implications that the transient aurora and energetic event are likely associated with the mass loading and are basically independent of the solar wind; that is, they are “internally driven” processes, as recently argued in Kimura et al (, ) and other studies.…”
Section: Resultssupporting
confidence: 81%
“…This correspondence implies that the transient aurora is, in some cases, forced to occur due to the solar wind disturbance. On DOY 142 in 2017, when Juno detected a solar wind forward shock arriving at Jupiter, Hisaki observed the transient aurora with one of the largest peak powers that has been measured through the entire Hisaki observing period from November 2013 to July 2016 (Kimura et al, ; Nichols et al, ). This solar wind associated brightening was also fragmentally observed by Cassini (Tsuchiya et al, ), supporting the idea suggested by the present study that the transient aurora is correlated with the solar wind disturbance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, JAXA's Hisaki satellite has been monitoring UV emissions from the Io plasma torus and Jovian auroral emissions since 2013. Kimura et al [] report on Hisaki observations made, while Juno was approaching Jupiter. They show a similar brightening of the aurora on 21 May 2016 as reported by Nichols et al [] in response to a solar wind compression region.…”
Section: Magnetospherementioning
confidence: 99%